Suboptimal Exposure to Anti‐TB Drugs in a TBM/HIV+ Population Is Not Related to Antiretroviral Therapy. Issue 3 (6th December 2017) - Török, ME; Aljayyoussi, G; Waterhouse, D; Chau, TTH; Mai, NTH; Phu, NH; Hien, TT; Hope, W; Farrar, JJ; Ward, SA
Abstract : A placebo‐controlled trial that compares the outcomes of immediate vs. deferred initiation of antiretroviral therapy in HIV +ve tuberculous meningitis (TBM) patients was conducted in Vietnam in 2011. Here, the pharmacokinetics of rifampicin, isoniazid, pyrazinamide, and ethambutol were investigated in the presence and absence of anti‐HIV treatment in 85 patients. Pharmacokinetic analyses show that HIV therapy has no significant impact on the pharmacokinetics of TB drugs in this cohort. The same population, however, displayed generally low cerebrospinal fluid (CSF) and systemic exposures to rifampicin compared to previously reported HIV –ve cohorts. Elevated CSF concentrations of pyrazinamide, on the other hand, were strongly and independently correlated with increased mortality and neurological toxicity. The findings suggest that the current standard dosing regimens may put the patient at risk of treatment failure from suboptimal rifampicin exposure, and potentially increasing the risk of adverse central nervous system events that are independently correlated with pyrazinamide CSF exposure.